Seleções de modelos de regressão não lineares e aplicação do algoritmo saem na avaliação genética do crescimento de bovinos Nelore - Natascha Almeida Marques da Silva (2010)
This study aimed to evaluate cluster analysis in classifing and selecting non linear models to describe Nellore beef cattle growth based on different goodness of fit criteria tests. A total of 12 non linear models were evaluated based on the following criteria::determination coefficient (R2), error mean square (QME), Akaike information criterion (AIC), Bayesian information criterion (BIC), mean quadratic error of prediction (MEP) and predicted determination coefficient (R2p). The Brody model showed the best goodness of fit for this data set.